You canâ€™t b. cereus: an unusual presentation of bacillus cereus - Hamant, Laura; Samareh-Jahani, Farmin; Muna Aguon MD, Paul; Swofford DO, Brenen; Marston MD, Thomas; Nanda MD, Alisha; Crawford MD, Julie (International Journal of Medicine, 2018)
We present a case of a 74-year- old male with a complicated medical history who was admitted to theWe present a case of a 74-year-old male with a complicated medical history who was admitted to the medical floor for evaluation and management of failure to thrive and malnutrition. On hospital day 9 he became febrile and blood cultures were found to be positive for B. cereus and Enterobacter cloacae, which were persistent. He had an extensive negative workup for the cause of his bacteremia, however, we present a number of possibilities from his presentation and a literature review. Our case was consistent with other cases in the literature as our patient could be considered immunocompromised secondary to malnutrition and type II diabetes. B. cereus in blood cultures is often considered a contaminant but can be true bacteremia and should be worked up if multiple blood cultures are positive or if there is a clinical suspicion.Â Â